8.5 Combined Fetal Fibronectin and Saliva Progesterone Measurement for Prediction of Spontaneous Preterm Birth. (9th June 2014) - Carter, J; Hezelgrave, N; Seed, P; Tribe, R; David, A; Lachelin, G; Shennan, A; Poston, L
Abstract : Introduction: Low saliva progesterone concentrations are associated with spontaneous preterm birth (SPTB) in high risk women. 1 This study further evaluated the combined use of fetal fibronectin (fFN) and saliva progesterone for SPTB prediction. Methods: A predefined secondary analysis undertaken on a subgroup of women from a prospective cohort (n = 1216) of asymptomatic women at high risk of SPTB. Participants provided at least one saliva sample between 20 +0 and 28 +6 weeks' and some underwent a qualitative fFN test (Hologic™; positive test results ≥50 ng/ml). Saliva progesterone concentrations were measured by ELISA (Salimetrics™). Primary end point was SPTB or rupture of membranes with delivery before 34 weeks'. Exclusions: women with iatrogenic PTB before 34 weeks' and women on progesterone supplementation or in the OPPTIMUM trial. Results: Overall, 638 women with paired saliva progesterone and fFN results (22 +0 and 25 +6 weeks') were identified with a SPTB rate <34 weeks' of 4.5%. A saliva progesterone concentration of <280 ng/l was associated with an odds ratio for delivery <34 weeks' of 3.81 (95% CI: 1.34 to 10.83); for fFN, the receiver operating characteristic curve (ROC) area for SPTB <34 weeks' was 0.61 (0.53 to 0.70). Combination of tests improved the ROC area [0.67 (0.56 to 0.78)]. In fFN negative women (n = 583), low saliva progesterone concentrations were associated with greater risk of SPTB <34 weeks' [positive likelihood ratio 3.4 (1.34 to 8.71)]. Conclusions: Saliva progesterone measurement may be useful for prediction of SPTB in high risk women as an adjunct to fFN testing. Reference: Lachelin GCL, et al . BJOG 2009;116:1515–9